Pre-Harvest Ethephon Application influences Growth and Development of Banana in Chitwan, Nepal - Shrestha, Bishal; Shrestha, Sheela (Multi-Disciplinary Explorations: The Kasthamandap College Journal, 2023)
Available with the full text.